Self-exited generator system of RF-power supply of the one-section linear ion accelerator - Lobzov, L.D.; Shulika, N.G. (Вопросы атомной науки и техники, 2001)
The paper presents the block-diagram of a RF-power supply system of a single-section linear ion accelerator and the results of experiments on studying its mode of operation with changing the parameters of circuits of positive back couling of the radio-frequency (RF) amplifier channel.